Fusarium tricinctum T-2 Toxin Inhibits Auxin-promoted Elongation in Soybean Hypocotyl - Stahl, Catherine (1973)
T-2 toxin, a mycotoxin produced by Fusarium tricinctum, inhibited elongation of excised hypocotyl sections of Glycine max var. Hawkeye 63. Auxin-promoted elongation was inhibited more severely than was control elongation, and a 1 hour preincubation of 5 μm toxin prevented the induction of a faster rate of elongation by auxin. While the inhibition of elongation by cytokinin was similar to that of the toxin, the mode of action of the two compounds appeared to be different, i.e. their effects on elongation were additive, and only kinetin promoted radial enlargement. Toxin treatment did not diminish cytokinin-induced radial enlargement. The properties of the plasma membrane, as measured by electrolyte leakage, were not affected by the toxin.